Paul Celan in Translation: "Du sei wie du" - John Felstiner (Studies in 20th & 21st Century Literature, 1983)
Translating the lyric poetry of Paul Celan, especially his later poems, carries not only the endemic challenge and difficulty of any verse translation, but the added incentive of doing justice to a writer whose whole recourse after the Holocaust—whose sanctuary, if he was to have any at all—he sought in language itself, specifically in the Muttersprache, the mother tongue that was as well the tongue of those who murdered his mother and father. This essay exposes a process of translating "Du sei wie du" (1970), which perhaps more than any other poem by Celan, at once solicits and defies translation, moving as it does from modern to medieval German, and closing with Hebrew words from Isaiah— a messianic imperative that shows Celan verging as ever on his Jewish identity.
Keywords: lyric poetry; Paul Celan; poetry; poem; endemic; verse translation; translation; Holocaust; language; Muttersprache; mother tongue; Du sei wie du; modern; medieval; German; Hebrew; Isaiah; messianic imperative; Jewish identity